2018
DOI: 10.5812/jhealthscope.55353
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Hydrogen Inhalation on Temporary Threshold Shift Following Simultaneous Exposure to Noise and Carbon Monoxide in Guinea Pigs

Abstract: Background: People might simultaneously be exposed to noise and carbon monoxide in occupational settings. The previous studies revealed that the inhalation of molecular hydrogen (H2) exerts some healing effects on multiple diseases including hearing loss. Objectives: The levels of free radicals have been shown to increase due to the exposure to noise plus carbon monoxide. This study examined the possible protective effects of hydrogen inhalation following simultaneous exposure to noise and carbon monoxide in G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Fransson et al 28 found less ABR threshold shifts, OHC loss, and damage to IHC synaptic structures from 2-hour noise exposure at 115 dB SPL when immediately followed by the same H 2 treatment as in the study presented here. Bagheri et al 29 found less ABR threshold shifts from 6-hour noise exposure at 105 dB SPL per day for 5 days in combination with the asphyxiant carbon monoxide when immediately followed by exposure with gaseous H 2 (2%) 5 hours per day for 5 days. Similar to those results, 27 - 29 acoustic trauma was not fully prevented in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fransson et al 28 found less ABR threshold shifts, OHC loss, and damage to IHC synaptic structures from 2-hour noise exposure at 115 dB SPL when immediately followed by the same H 2 treatment as in the study presented here. Bagheri et al 29 found less ABR threshold shifts from 6-hour noise exposure at 105 dB SPL per day for 5 days in combination with the asphyxiant carbon monoxide when immediately followed by exposure with gaseous H 2 (2%) 5 hours per day for 5 days. Similar to those results, 27 - 29 acoustic trauma was not fully prevented in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Bagheri et al 29 found less ABR threshold shifts from 6-hour noise exposure at 105 dB SPL per day for 5 days in combination with the asphyxiant carbon monoxide when immediately followed by exposure with gaseous H 2 (2%) 5 hours per day for 5 days. Similar to those results, 27 - 29 acoustic trauma was not fully prevented in the present study. In particular, OHC loss was unsatisfactorily high despite prompt H 2 treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation